2000
DOI: 10.1007/s002590000366
|View full text |Cite
|
Sign up to set email alerts
|

Non-invasive assessment of the effect of cardiac sympathetic innervation on metabolism of the human heart

Abstract: The role of cardiac sympathetic nerves in the regulation of myocardial metabolism is not well defined. Owing to the presence of incomplete reinnervation, heart transplant recipients provide a unique model to study the effects of efferent sympathetic innervation. Using this model, we sought to determine the influence of cardiac sympathetic signals on substrate utilisation and overall oxidative metabolism. In 21 transplant recipients, positron emission tomography was applied to determine sympathetic innervation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
1

Year Published

2001
2001
2019
2019

Publication Types

Select...
4
3
2

Relationship

4
5

Authors

Journals

citations
Cited by 32 publications
(9 citation statements)
references
References 24 publications
0
8
1
Order By: Relevance
“…Previous work has shown that sympathetic reinnervation contributes to partial restoration of exercise capacity 29 and plays a role for regulation of myocardial blood flow and metabolism. 30,31 In the present study, however, cardiac work, oxygen consumption, and efficiency at rest were not different between reinnervated and denervated transplant recipients. Additionally, there was no regional difference for contractile performance or oxygen consumption in reinnervated and denervated territories.…”
Section: Discussioncontrasting
confidence: 40%
“…Previous work has shown that sympathetic reinnervation contributes to partial restoration of exercise capacity 29 and plays a role for regulation of myocardial blood flow and metabolism. 30,31 In the present study, however, cardiac work, oxygen consumption, and efficiency at rest were not different between reinnervated and denervated transplant recipients. Additionally, there was no regional difference for contractile performance or oxygen consumption in reinnervated and denervated territories.…”
Section: Discussioncontrasting
confidence: 40%
“…Patients were prospectively selected from a large group of Ͼ500 patients who had undergone transplantation since 1981 at the Herzchirurgische Klinik der Ludwig-Maximilians-Universität München to participate in projects aiming at characterization of allograft reinnervation and its physiological relevance. 8,10,12 Selection was based on availability, willingness to participate, and absence of acute rejection, clinically significant transplant vasculopathy (defined by absence of significant coronary stenoses at angiography and/or normal dobutamine stress echocardiography), allograft dysfunction, diabetes mellitus, other symptomatic noncardiac diseases, and medication known to interfere with presynaptic catecholamine uptake. Twenty-three of the patients had undergone transplantation because of ischemic cardiomyopathy and the other 54 because of idiopathic cardiomyopathy.…”
Section: Patientsmentioning
confidence: 99%
“…The occurrence of subsequent partial reinnervation of the left ventricle has been demonstrated in various studies, [1][2][3][4][5][6] and the physiological importance of this phenomenon has been supported by description of beneficial effects on regulation of myocardial blood flow, 7 metabolism, 8,9 and exercise performance. 10,11 Because of the increasing evidence that restoration of sympathetic innervation is advantageous for transplant recipients, approaches to support reinnervation are of interest, and a more detailed understanding of clinical determinants of reinnervation is desirable.…”
mentioning
confidence: 99%
“…Several groups studied the in reinnervation the transplanted heart as a model of regional denervation. They showed that the sympathetic innervation is associated with improvement of endothelial-dependent vascular reactivity regulation, response of heart rate, and ventricular function [45][46][47]. These results support the functional importance of reinnervation of transplanted hearts, and may guide further therapies employing neuronal growth factor or stem cells.…”
Section: The Transplanted Heartmentioning
confidence: 53%